Aspects of Teaching Poetry at the Secondary Level - Tamang, Dipak; Sigdel, Madhu Sudan (Patan Prospective Journal, 2025)
This paper aims to explore the aspects focused on while teaching poems from the Compulsory English textbook in the current Secondary level. The objectives of the study were to determine how the basic components of language are presented to students in their poetry learning class. It also aims to gather information on whether the poetic qualities are addressed or not. The aspects of pronunciation, vocabulary, and meaning of the poem were tested in the form of multiple-choice and ‘yes’ or ‘no’ items. Qualitative and quantitative methods were used to interpret the collected data. The data was collected by supplying a set of questionnaires to one hundred students studying in grade nine from a number of schools in Kathmandu Valley. These participants were from public and private schools. Based on the degree of occurrence of the selected items, the results were illustrated and broadly analyzed. The data shows that about one-fifth of the students have focused on pronunciation. Similarly, a larger number of students have shown their emphasis on the aspect of meaning of the poem, whereas the remaining majority of the students have shown their interest in the vocabulary aspect of the poem.